Impact of the vibrocathode on the patterns and properties of electrolytic copper powders - Marina V Korchagina; Alexander A. Naumenko; Valery M. Lipkin (Advanced Engineering Research)
Methods for obtaining ultrafine copper powders from the etching waste of the printed circuit boards are described. Modes of obtaining copper powder in the anode-synthesized chloride-ammonium electrolyte using vibrocathode that allows intensifying the process as compared to the similar one at the stationary cathode by reducing diffusion layer are described. The productivity of copper powder obtaining in the offered terms is 0.25 g/(cm2·h), mean particle size is 3-4 microns. High efficiency of the process compared with the use of sulphate electrolytes, and a positive effect of the shape and size of the obtained copper powder on the processes of alloying Fe-based materials are reported. Properties of the antifriction materials doped with the obtained cathode copper powder in comparison with the materials alloyed with the PMS-1copper powder are considered. The effect of the working properties improvement of the samples doped with copper powder obtained from a copper-ammonium solution is observed.